Emotional disregulation, rumiation and suicide ideation in students of general studies of a university Metropolitan Lima public - Velásquez Centeno, Carlos (2020)
In the present investigation, the relationships between emotional dysregulation, rumination and suicidal ideation are addressed. The study first includes the elucidation of the theoretical concepts of the variables involved, understanding them under a reference paradigmatic framework called "functional contextualism". Regarding the method, the variables are measured by means of the Difficulties Scales of Emotional Regulation, Ruminative Responses and Positive and Negative Suicidal Ideation, all applying to a sample of 1330 students from the School of General Studies of a Public University of Lima, enrolled in the Academic year 2018. The results show that there are significant correlations between emotional dysregulation, rumination and suicidal ideation, the highest being found between emotional deregulation and rumination. In particular, it is also seen that those entering the humanities area are on average more vulnerable to suffer them.